2008
DOI: 10.1002/hbm.20646
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of personally familiar faces: Parents, partner and own faces

Abstract: Investigations of the neural correlates of face recognition have typically used old/new paradigms where subjects learn to recognize new faces or identify famous faces. Familiar faces, however, include one's own face, partner's and parents' faces. Using event-related fMRI, we examined the neural correlates of these personally familiar faces. Ten participants were presented with photographs of own, partner, parents, famous and unfamiliar faces and responded to a distinct target. Whole brain, two regions of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 77 publications
6
89
0
1
Order By: Relevance
“…These photographs were cropped and converted to grayscale images with equal luminance. In addition, a "ghost face" stimulus image representing the superimposition of all group members' faces was prepared for each group following methods used in prior face perception research (29). The face-viewing task implemented a rapid event-related design that included 10 repetitions of each stimulus face presented in pseudorandomized order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These photographs were cropped and converted to grayscale images with equal luminance. In addition, a "ghost face" stimulus image representing the superimposition of all group members' faces was prepared for each group following methods used in prior face perception research (29). The face-viewing task implemented a rapid event-related design that included 10 repetitions of each stimulus face presented in pseudorandomized order.…”
Section: Methodsmentioning
confidence: 99%
“…Faces were presented for 1,000 ms and interstimulus intervals (ISIs) consisting of white fixation cross on black background were jittered between 1,500 ms and 11,500 ms (mean duration of ISI = 3,500 ms). Perceivers viewed faces of targets while performing a simple cover task (29) to maintain their alertness throughout. Specifically, participants were instructed to press a button with their pointer (second) finger each time a group member's face was presented and a different button with their ring (fourth) finger each time a "ghost face" was presented (∼9% of total presentations).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that famous faces might be represented as icons or celebrity snapshots rather than as faces per se. Taylor et al (2009) showed in a brain imaging study that brain activation induced by personally familiar faces was more widespread and bilaterally distributed, while famous faces elicited activity lateralized to the right hemisphere in the same areas as unfamiliar faces. between the specific low-level stimulus properties and featureselective neurons in the corresponding cortical areas, for example, orientation-specific neurons in visual area V1 as a basis for the tilt aftereffect.…”
Section: Figural Aftereffectsmentioning
confidence: 99%
“…Two studies comparing self-face processing to a familiar face processing found activity in the medial frontal gyrus, one on the right (Platek, Loughead, Gur, Busch, Ruparel, Phend et al, 2006) and one on the left (Platek & Kemp, 2009). With unfamiliar control faces, two studies reported activity in the right (Platek & Kemp, 2009;Sugiura et al, 2000) and one bilateral activity (Taylor, Arsalidou, Bayless, Morris, Evans, & Barbeau, 2009) in the medial frontal gyrus. In a study comparing recognition of the self to recognition of personally familiar faces related (i.e.…”
Section: Selfmentioning
confidence: 99%